Creating Multicultural Opportunities in Music Teacher Education: Sharing Diversity Through Online Competitions - Karkina, Svetlana; Singh, Balwant; Batyrshina, Gulnara; Nurgayanova, Nelya (Frontiers in Education, 2022)
Facing the emergency of COVID19 pandemic, Higher Education demonstrated new challenges which required to design and implement new types of multicultural interaction by the means of online tools. Online competition is the new form of international interaction popularity of which is growing up rapidly nowadays. The aim of this study was to assess the advantages of online competitions in promoting multicultural opportunities in music teachers' education. The research work was organized in two stages at Kazan Federal University (Russia) in the collaboration with Partap College of Education (India) where two online competitions- an international competition of students` research works and a vocal singing competition were organized. The jury committee included nine members who represented three countries (Russia, India, and Armenia). During the competitions, 95 students` research reports and 75 vocal performance records were collected. The results were analyzed by using the average rating method. The most significant criteria to assess the research work included- the knowledge in the field of cultural diversity and the research scope demonstrating global experience. The vocal records were compared by the criteria such as art and technical level of performance, artistic style, expressive performance, and others. The comparative analysis was used for studying cultural diversity in the vocal records which presented more than fifteen different cultures delivering Western and Eastern musical traditions featured by differences in genres, fret-harmonic structure, performance style, and national instruments. The obtained results showed a high level of sharing music cultural diversity through these two online competitions. It was concluded that online competition demonstrates advantages in sharing the diversity of music cultures. The criteria based on multiculturality allows evaluating competitive works objectively focusing at the same time on their diversity. The implementation of a multicultural approach in online competitions will promote sharing the world music experience diversities in order to preserve each art tradition as original cultural heritage.